2005
DOI: 10.1016/j.neures.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial diversity in gene expression for VDCCγ subunit family in developing and adult mouse brains

Abstract: The γ subunit of voltage-dependent Ca 2+ channels (VDCCs) is characterized by molecular diversity and regulation of AMPA-type glutamate receptors as well as VDCCs. In the present study, we examined expressions for the VDCCγ1-8 subunit mRNAs in developing and adult mouse brains by in situ hybridization. In adult brains, the γ2 and γ7 subunit mRNAs were widely expressed in various grey matter regions with the highest level in cerebellar Purkinje cells and granule cells. The γ3 and γ8 subunit mRNAs predominated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
144
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(155 citation statements)
references
References 28 publications
11
144
0
Order By: Relevance
“…On the contrary, ␥-5 is enriched in microsomal fraction (P3) and synaptosomal fraction but not in the PSD. This observation is consistent with the report that ␥-5 is mainly expressed in cerebellar Bergmann glia (Fukaya et al, 2005), which lack a PSD domain. As controls, we show that PSD-95 and synaptophysin are enriched in the PSD and synaptic vesicle fractions, respectively.…”
Section: ␥-7 Is Enriched In the Psd And Binds To Psd-95supporting
confidence: 93%
See 2 more Smart Citations
“…On the contrary, ␥-5 is enriched in microsomal fraction (P3) and synaptosomal fraction but not in the PSD. This observation is consistent with the report that ␥-5 is mainly expressed in cerebellar Bergmann glia (Fukaya et al, 2005), which lack a PSD domain. As controls, we show that PSD-95 and synaptophysin are enriched in the PSD and synaptic vesicle fractions, respectively.…”
Section: ␥-7 Is Enriched In the Psd And Binds To Psd-95supporting
confidence: 93%
“…Mice lacking ␥-8 have an 80 -90% decrease in extrasynaptic AMPA receptor in hippocampal neurons (Rouach et al, 2005;Fukaya et al, 2006). The residual AMPA receptor function in the hippocampus of ␥-8 knockouts likely reflects expression of ␥-2 and ␥-3 in these neurons (Fukaya et al, 2005). The finding that AMPA receptor responses are present in cerebellar Purkinje cells of stargazer mice has been perplexing because only ␥-2, and not ␥-3, ␥-4 or ␥-8, occurs in these neurons (Fukaya et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of in situ hybridization and immunohistochemistry, γ-7 is expressed in other cerebellar neuronal cell types including stellate cells (SCs) and granule neurons (CGNs) (11,12,14). Biochemical and heterologous expression studies have shown that γ-7 is capable of binding to AMPARs and enhancing AMPAR trafficking and gating in stg CGNs, albeit less effectively than γ-2 (12, 16).…”
mentioning
confidence: 99%
“…Of particular interest is TARP γ-7, which is expressed throughout the brain but exhibits high levels of expression, along with γ-2, in cerebellar Purkinje cells (PCs) (11)(12)(13)(14). Deleting γ-2 on its own causes a ∼60% reduction in AMPAR-mediated synaptic currents in PCs (14,15).…”
mentioning
confidence: 99%